Periodic solutions of pulse evolutionary systems with unbounded nonlinearities - Rogovchenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The conditions are established, under which periodic solutions of pulse evolutionary systems with unbounded (in x) operators on the right-hand sides exist and are stable.